2024
DOI: 10.1109/access.2020.3020791
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Visual Error Correction Method for VR Image of Continuous Aerobics

Abstract: In recent years, with the rapid development of virtual reality technology, the visual error correction of continuous aerobics image in virtual environment is of great value to the analysis of Aerobics technology. The main purpose of this paper is to study the visual error correction algorithm of VR image of continuous aerobics. This paper mainly introduces the overview of VR technology, characterist ics and aerobics, some algorithms of visual error correction. This article selects a continuous aerobics coach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The improvement of the ability of aerobics athletes from sitting to standing is conducive to the improvement of daily activities and quality of life. 11 The results of this study showed that, compared with the control group, after 4 weeks of intervention, the SF-36 in the intervention group only increased the scores of 3 dimensions of physical function, somatic pain and general health, and the scores of all 8 dimensions increased after 8 weeks; Comparing the differences in the scores of each dimension between the three time points, they were all increased after 8 weeks compared with before the intervention, indicating that elastic band training can improve the quality of life of aerobics special athletes in the early stage of frailty, manifested in physiological function, physiological function, body pain, general Health, energy, social function, emotional function, and mental health are eight aspects. 12 The other five aspects are improved slowly.…”
Section: Results and Analysismentioning
confidence: 99%
“…The improvement of the ability of aerobics athletes from sitting to standing is conducive to the improvement of daily activities and quality of life. 11 The results of this study showed that, compared with the control group, after 4 weeks of intervention, the SF-36 in the intervention group only increased the scores of 3 dimensions of physical function, somatic pain and general health, and the scores of all 8 dimensions increased after 8 weeks; Comparing the differences in the scores of each dimension between the three time points, they were all increased after 8 weeks compared with before the intervention, indicating that elastic band training can improve the quality of life of aerobics special athletes in the early stage of frailty, manifested in physiological function, physiological function, body pain, general Health, energy, social function, emotional function, and mental health are eight aspects. 12 The other five aspects are improved slowly.…”
Section: Results and Analysismentioning
confidence: 99%